Investing in renewable energy : making money on green chip stocks - Siegel, Jeffrey, 1970- (Angel series., 2008)
Investment advisor Jeff Siegel maintains that in the next 10 to 15 years, the price of renewable energy will fall dramatically, allowing the industry not only to compete on a level playing field, but to offer energy at a price that will be cheaper than oil, natural gas, and coal. Investors who understand this market will be the first to uncover some very profitable opportunities. Filled with in-depth insights and practical advice, this book will show readers how to tap into this market early, and logically, in order to capture unparalleled profits.--From publisher description.